Sistem Pengelolaan dan Pemanfaatan Harta Pusaka Masyarakat Minangkabau dalam Karya Wisran Hadi - Irfani Basri; Ellya Ratna (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2020)
This reasearch describes about management and the usage system of harta pusaka in novels wrote by Wisran Hadi. The novel that became the object of this research titled Orang-orang Belanti dan Negeri Perempuan. In this research it is found that basicaly in minangkabau culture they have some rules use as they have in their society. But in fact, thereis also misunderstanding in managing tanah pusaka by man and the government because of thereason of people need. Butital sotells that there is a case that follow the rule in society. For example, in Bundo’s character, as one of the person who receive harta pusaka and can use it without have to overtaking other’s rights. Then, she also canuseit for all. Meanwhile, man that has power tomanage Harta pusaka does not have right to own it.